Editor's Note = Note du directeur [12, Fall 1983] - Kealey, Gregory S. (Labour / Le Travail, 1983)
Takes note that a previously published book review by Jacques Roulliard is being reprinted with corrections in the current issue.

Editor's Note = Note du directeur [11, Spring/Printemps 1983] - Kealey, Gregory S. (Labour / Le Travail, 1983)
Takes note of the poetry published in the issue, including an accompanying essay. Bryan Palmer will soon be contributing as the review editor. Following an SSHRCC investigation of alternative formats, the print publication of the journal will continue to have primacy over microfiche.

Economy and Society During the French Regime, to 1759 - Cross, Michael S.; Kealey, Gregory S. (McClelland and Stewart, 1983)
...As an introduction to the birth and growth of society in New France, the scholarly articles contained in the volume draw from the translated writings of Marcel Trudel and Fernand Ouellet, two of French Canada's leading historians. As well, contributions from Bruce Trigger and Calvin Martin look at the impact of European society on the culture of Native peoples. Together with articles on land use and labour, this informative volume offers a discerning view of the earliest of French Canada - the life of the habitant, the raucous beginning of the first craft brotherhoods, the movement toward a new social order which early European inhabitants took to with a "missionary zeal." By exploring the social roots of modern day Quebec [the book] sheds new light on our understanding of French Canada. –Publisher's description
OCLC: 1332769473
Keywords: Canada; Canada Conditions sociales Jusqu'à 1763; Canada Conditions sociales Jusqu'à 1867 Discours; essais; conférences; Canada Conditions économiques Jusqu'à 1763; Canada Conditions économiques Jusqu'à 1867 Discours; essais; conférences; Canada Economic conditions To 1763; Canada Economic conditions To 1867; Canada Social conditions To 1763; Canada Social conditions To 1867; Economic history; Kanada; Social conditions; Sozialgeschichte 1642-1759; To 1763

The Consolidation of Capitalism, 1896-1929 - Cross, Michael S.; Kealey, Gregory S. (McClelland and Stewart, 1983)
[This book] is the fourth of a five-volume series of readers designed to present an overview of Canada's social history, encompassing such topics as economic development, social structure, politics, religion, work and workers, and the changing role of women. In this volume the editors have assembled a series of scholarly essays examining such historic developments as government support of big business and the concentration of capital, the decline of craft unionism in Hamilton factories, the business impetus behind municipal reform, and the circumstances for working women in the 1920s. Articles such as Donald Avery's account of labour exploitation in the hiring of "foreign" navvies to build railroads in Western Canada and Don Macgillivray's analysis of state intervention and the use of troops in strikes among Cape Breton miners and steel workers in the 1920s highlight the issues and controversies which makes this one of the most telling chapters of Canada's social history. –Publisher's description
OCLC: 10120220
Keywords: 1918-1945; Aufsatzsammlung; Canada; Canada Conditions sociales; Canada Conditions sociales 1867-1918; Canada Conditions sociales 1918-1930; Canada Conditions économiques; Canada Conditions économiques 1867-1918; Canada Conditions économiques 1918-1945; Canada Economic conditions; Canada Economic conditions 1867-1918; Canada Economic conditions 1918-1945; Canada Social conditions; Canada Social conditions 1867-1918; Canada Social conditions 1918-1930; Economic history; Geschichte 1896-1929; Kanada; Social conditions; Sozialgeschichte 1896 - 1929; Wirtschaft